Validity and Reliability of a Brief Scale of Intention to Vaccinate Against COVID-19 in a Peruvian Sample - Wilter C. Morales-García; Salomón Huancahuire-Vega; JackSaint Saintila; Percy G. Ruiz Mamani (SAGE Publishing, 2022)
Objective: This study aimed to analyze the psychometric properties of a brief scale measuring intention to vaccinate against COVID-19 in a Peruvian sample in the context of the current pandemic. Methods: A cross-sectional and instrumental study was carried out. A total of 547 Peruvian citizens selected through non-probability convenience sampling participated. Considering existing theories of vaccination hesitancy, 12 items were proposed that evaluate the intention to vaccinate against COVID-19 and the internal structure was evaluated through exploratory and confirmatory factor analysis. Reliability was analyzed with the ordinal alpha coefficient. Results: The exploratory factor analysis yielded a structure of 2 oblique factors that explain 69% of the total variance and the items saturated between 0.52 and 0.97. The confirmatory factor analysis showed that, of 4 models analyzed, the fourth model that was composed of 6 items presented optimal indices of goodness-of-fit ( X 2  = 11.089, P  = .197, CFI = 0.999, TLI = 0.999, RMSEA = 0.034 [IC 90%, 0.000-0.077], SRMR = 0.016). Reliability analysis through the ordinal alpha coefficient yielded that the brief scale of intention to vaccinate against COVID-19 has adequate internal consistency (α = .91). Conclusions: The brief scale of intention to vaccinate against COVID-19 presents adequate psychometric properties that demonstrate validity and reliability and can be used in future research and clinical practice.